Angiotensin (1-7) Alleviates Postresuscitation Myocardial Dysfunction by Suppressing Oxidative Stress Through the Phosphoinositide 3-Kinase, Protein Kinase B, and Endothelial Nitric Oxide Synthase Signaling Pathway. Issue 1 (July 2021) - Zhu, Li; Liu, Zhen; Huang, Li-Ping; Zhou, Hou-Rong; Cao, Yu; Yang, Xue-Ping; Wang, Bing-Jin; Yang, Zi-Li; Chen, Jing
Abstract : Abstract: There is increasing evidence that angiotensin (1-7) [Ang (1-7)] is an endogenous biologically active component of the renin–angiotensin system. However, the role of the Ang (1-7)-MasR axis in postresuscitation myocardial dysfunction (PRMD) and its associated mechanism are still unclear. In this study, we investigated the effect of the Ang (1-7)-MasR axis on myocardial injury after cardiac arrest-cardiopulmonary resuscitation-restoration of spontaneous circulation. We established a model of oxygen/glucose deprivation-reperfusion in myocardial cells in vitro and a rat model of cardiac arrest–cardiopulmonary resuscitation–restoration of spontaneous circulation in vivo. The cell apoptosis rate and the expression of the superoxide anion 3-nitrotyrosine were decreased in the Ang (1-7) group in vitro and in vivo. The mean arterial pressure was decreased, whereas +LVdp/dtmax and −LVdp/dtmax were increased in rats in the Ang (1-7) group. The mRNA and protein levels of Ang II type 1 receptor, MasR, phosphoinositide 3-kinase, protein kinase B, and endothelial nitric oxide synthase were increased in the Ang (1-7) group in vivo. These results indicate that the Ang (1-7)-MasR axis can alleviate PRMD by reducing myocardial tissue damage and oxidative stress through activation of the phosphoinositide 3-kinase–protein kinase B–endothelial nitric oxide synthase signaling pathway and provide a new direction for the clinical treatment of PRMD. Abstract : Supplemental Digital Content is Available in the Text.